DEVELOPMENT OF A METHOD AND DEFINITION OF A NEW TRAFFIC SAFETY CONDITION IN A MULTITHREADING STATE BASED ON MATHEMATICAL MODELING - Sergey V. Zykov; Svyatoslav A. Zolotukhin; Maria A. Zolotukhina (Модели, системы, сети в экономике, технике, природе и обществе, 2023)
Background. All attention is focused on reducing the number of accidents on an unfavorable section of the Altufyevsky highway in the area of 5 intersections. Such incidents become aggravating circumstances for nearby infrastructure facilities, such as: shopping malls, shops, cafes, there are also metro stations on a busy site. The endless flow of people and cars, public transport stops, etc. require new security conditions. Materials and methods. To carry out the analysis, methods of modeling, statistics and data mining were used, namely: to simulate the traffic flow on a particular road section, to determine the problem of the site, and to apply the simulation methodology to derive an algorithm for improving the quality of traffic, defining new safety conditions and improving the characteristics of determining the parameters of adverse events – these are the main aspects of the study. Results. A model of multithreaded traffic in a software environment has been developed, an analysis of the traffic flow has been carried out to improve the method used and to derive new conditions for safe traffic on multithreaded road sections and intersections. A decision-making model is derived by creating a training sample from the video stream of the characteristics presented in the article. Conclusions. The presence of traffic lights is one of the safety conditions, but it has some nuances. All stages of detection of adverse situations and new solutions are spelled out in the article.